Sikap Memediasi Kepedulian Lingkungan terhadap Niat Beli Produk Le Minerale - Nyoman Dewi Pitaloka Cahyadi; Ni Putu Dera Yanthi; Ni Nyoman Dian Sudewi; Putu Ayu Trisna Febrianty (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Bottled drinking water (BDW) is one of the largest contributors to plastic waste, the level of consumer concerns to switch to more environmental friendly products is needed to reduce plastic waste. This study designs to analyze the level of consumer concerns and consumer attitudes in influencing consumer purchase intentions for Le Minerale products in Denpasar. The purposive sampling method was used to collect 130 respondents residing in Denpasar. The data was processed using the PLS method, which obtained the results that the level of environmental concern and consumer attitudes have a significant influence on consumer purchase intentions for Le Minerale products in Denpasar. This study also found that consumer attitudes have a mediating role in the influence of the level of consumer concern on consumer purchase intentions on Le Minerale products in Denpasar. This study is expected to provide insight into the consumption of BDW that is more environmentally friendly, so that consumers can contribute and be responsible for environmental cleanliness with a sustainable impact.